Steroid injection in Orthopaedics: Does addition of lidocaine actually reduce pain? - Khanal, Krishna Raj; Pradhan, Rabindra Lal; Pandey, Bimal Kumar (Journal of Kathmandu Medical College, 2021)
Background: Local corticosteroid preparations are conventionally mixed with local anaesthetic agents to reduce pain during injection for various soft tissue affections in Orthopaedics. Although it can anaesthetise the area after injection, the infiltration process itself can be more painful because of low pH of the lidocaine.Objectives: To assess whether addition of lidocaine actually reduces pain during local steroid injection.Methods: This was a prospective comparative study conducted at Kathmandu Medical College over a period of nine months from June 2020 to February 2021 after obtaining ethical clearance. Patients requiring local corticosteroid injection for various indications in Orthopaedics were included by convenience sampling and divided into two groups. Out of 147 patients, 75 received steroid with lidocaine and 72 with normal saline. The Visual Analogue Score was recorded immediately along with injection in a scale of 0 to 10 where 0 meant no pain at all and 10 meant maximum pain imaginable. The difference in median Visual Analogue Score and the mean cost of injection between two groups was compared. Findings were analysed using SPSS v.20.Results: Median Visual Analogue Score in lidocaine group was 5 whereas in normal saline group was 4 (p-value = 0.33, Mann-Whitney U test). The mean cost of injection in lidocaine and normal saline groups were Nepali Rupees  339.3 ± 37.7 and 282.3 ± 36.7 respectively (p